(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
The article presents and analyzes two cases of criminalization of people in contexts of vulnerability in the province of Salta- Argentina during the years 2018 and 2021. It analyzes the energetic dimension of social inequality that crosses these cases and incorporates the gender perspective to account for the impact of the forms of access to energy in care tasks, the process of feminization and "moral" level that these acquire in the penal-punitive system.